Associations between adolescents’ cognitive distortion and misperceptions about cigarette smoking - Jia Cindy Xinshan; Cheung Chau-Kiu; Li Li (Psihologija)
Preventing the initiation of cigarette smoking is a core concern for adolescents’ health in schools. Sufficient evidence has shown that one’s smoking behavior is susceptible to one’s misperception about the smoking status of proximate peers. However, the cognitive associates of the misperception remain largely uncharted. This study examines how cognitive distortion, which represents a cognitive error in information processing, associates with misperception of friends’ cigarette smoking status. The study surveyed 334 dyads of college students to assess their cognitive distortion and misperception with instruments such as the Cognitive Distortions Questionnaire. Logistic regression analyses revealed that cognitive distortion significantly associated with underestimation of the friend’s smoking status, especially among non-smokers. It implies reducing cognitive distortion may be useful for preventing cigarette smoking.